Early-Career Coordinated Distributed Experiments: Empowerment Through Collaboration - Pastor, Ada; Hernández-del Amo, Elena; Giménez-Grau, Pau; Fillol, Mireia; Pereda, Olatz; Flores, Lorea; Sanpera-Calbet, Isis; Bravo, Andrea G.; Martín, Eduardo J.; Poblador, Sílvia; Arroita, Maite; Rasines-Ladero, Rubén; et al. (Frontiers in Education, 2020)
Coordinated distributed experiments (CDEs) enable the study of large-scale ecological patterns in geographically dispersed areas, while simultaneously providing broad academic and personal benefits for the participants. However, the effective involvement of early-career researchers (ECRs) presents major challenges. Here, we analyze the benefits and challenges of the first CDE exclusively led and conducted by ECRs (i.e. ECR-CDE), which sets a baseline for similar CDEs, and we provide recommendations for successful CDE execution. ECR-CDEs achieve most of the outcomes identified in conventional CDEs as well as extensive benefits for the young cohort of researchers, including: (i) receiving scientific credit, (ii) peer-training in new concepts and methods, (iii) developing leadership and communication skills, (iv) promoting a peer network among ECRs, and (v) building on individual engagement and independence. We also discuss the challenges of ECR-CDEs, which are mainly derived from the lack of independence and instability of the participants, and we suggest mechanisms to address them, such as resource re-allocation and communication strategies. We conclude that ECR-CDEs can be a relevant tool to empower ECRs across disciplines by fostering their training, networking and personal wellbeing.